Towards a comprehensive understanding of football stadium tourism - Tim Edensor (2022)
Whereas stadium tourism is a growing area within sports tourism, football stadium tourism remains underexplored. Existing research largely focuses on match-day or heritage experiences, drawing on single case studies, with no current study comprehensively exploring the multiplicity of touristic experiences across a sizeable range of stadia. We address this neglect through an extensive investigation of football stadia as tourism destinations, using a novel methodology, latent Dirichlet allocation, to examine 28,298 TripAdvisor reviews of the 44 football stadia in the English Premier League and Championship (2019–2020 season), accompanied by a thematic analysis of reviews. This approach enables an investigation of multiple touristic experiences across many diverse sites. The study confirms previous findings about how stadia function as experiential sites of pilgrimage and heritage. However, two new dimensions of this visitor experience are revealed that demonstrate how stadia function as restaurants and possess prosaic and functional attributes that are significant dimensions of visitor experience.